Data assimilation constrains new connections and components in a complex, eukaryotic circadian clock model - Alexandra Pokhilko; Sarah K Hodge; Kevin Stratford; Kirsten Knox; Kieron D Edwards; Adrian W Thomson; Takeshi Mizuno; Andrew J Millar (Molecular Systems Biology)
Abstract Circadian clocks generate 24‐h rhythms that are entrained by the day/night cycle. Clock circuits include several light inputs and interlocked feedback loops, with complex dynamics. Multiple biological components can contribute to each part of the circuit in higher organisms. Mechanistic models with morning, evening and central feedback loops have provided a heuristic framework for the clock in plants, but were based on transcriptional control. Here, we model observed, post‐transcriptional and post‐translational regulation and constrain many parameter values based on experimental data. The model's feedback circuit is revised and now includes PSEUDO‐RESPONSE REGULATOR 7 (PRR7) and ZEITLUPE. The revised model matches data in varying environments and mutants, and gains robustness to parameter variation. Our results suggest that the activation of important morning‐expressed genes follows their release from a night inhibitor (NI). Experiments inspired by the new model support the predicted NI function and show that the PRR5 gene contributes to the NI. The multiple PRR genes of Arabidopsis uncouple events in the late night from light‐driven responses in the day, increasing the flexibility of rhythmic regulation.